Exploring the challenges faced by female executives in the Malaysian oil palm plantation industry: a qualitative study - Roslam, A. I. A.; N. H., Mohammad Azam; N. N. H., Aziz; Jamayah, Saili; J., Zulkefli; M. Z., Kamil; Z., Sapak; Sharifah Mazenah, Wan Yusuf; Abdul Rahman, Saili (Rynnye Lyan Resources, 2023)
Study regarding the life experiences of female executive planters in Malaysia's oil palm plantation sector is sparse. This gap is significant as Malaysia's plantation sector is beginning to hire more female employees, especially at the executive levels such as assistant manager and estate manager posts. Female employees account for 20-25% of the total plantation workforce in Malaysia, according to major palm oil companies. Despite their significant contribution and role in an oil palm plantation, females’ efforts have been overshadowed by their male colleagues. This raises the question of why this situation occurs and how it affects female executive planters in Malaysian oil palm plantations. Hence, this research aimed to establish and assess the individual experiences of female executive planters. The focus will be on the current situation of female executives in the oil palm plantation industry, together with the challenges faced by female executives when working in the oil palm plantation industry. A qualitative study was conducted with eight female executive planters who participate in the oil palm plantation industry in Peninsular Malaysia to identify their life experiences, assess the current situation, and explore the challenges faced working as executive planters in the oil palm plantation industry in Malaysia. Semi-structured interviews were used to collect data from the participants using the snowball sampling method based on the availability of female executive planters in Peninsular Malaysia. The data were analysed using Thematic Analysis (TA) and categorized into six themes. The analysis revealed that their current situation and challenges were associated with job nature, acceptance, physical work, safety, managing worker, and stereotypes. These findings were expected to have significant information to add to the literature on female roles and their participation in the oil palm plantation industry. Thus, it can help to formulate plans to enhance the situation for the female executive planter in the oil palm plantation industry in the future.